Azithromycin treatment response as a probe to attribute bacterial etiologies of diarrhea using molecular diagnostics: a reanalysis of the Antibiotics for Children with Severe Diarrhea (ABCD) trial - Cornick, Jennifer; Elwood, Sarah; Platts-Mills, James; Pavlinac, Patricia; Manji, Karim Premji; Sudfeld, Christopher R.; Duggan, Christopher P.; Dube, Queen; Bar-Zeev, Naor; Kotloff, Karen; Sow, Samba O.; Sazawal, Sunil; et al. (Frontiers in Microbiology, 2025)
BackgroundMulti-pathogen molecular diagnostics enhance our understanding of the pathogen-specific burden of diarrhea. However, attributing etiology remains challenging in high-burden settings where coinfections are common. The Antibiotics for Children with severe Diarrhea (ABCD) trial provides a unique opportunity to leverage azithromycin treatment response to identify bacterial diarrhea.MethodsWe analyzed data from 6,692 children with watery diarrhea enrolled in ABCD (2017 to 2019) who were randomized to receive azithromycin or placebo. We modelled the heterogeneity in the azithromycin treatment response by the enteric pathogen quantity detected by quantitative PCR using log-binomial regression.ResultsAzithromycin treatment response varied by pathogen quantity, with the strongest effect observed for Shigella. Each log₁₀ increase in Shigella quantity was associated with a 13% reduction (95% CI: 3–23%) in diarrhea risk at day 3 in the azithromycin group compared to placebo. We observed similar, though non-significant, trends for Vibrio cholerae, ST-ETEC, and tEPEC. In contrast, no association was found between pathogen quantity and azithromycin response for Campylobacter, LT-ETEC, or EAEC. These patterns remained consistent when evaluating hospitalization or death risk within 90 days.ConclusionThe observed associations between azithromycin treatment response and pathogen quantity for Shigella, Vibrio cholerae, ST-ETEC, and tEPEC support prior evidence that these pathogens are likely causes of diarrhea when present in high quantities. Conversely, the absence of a similar response pattern for Campylobacter, LT-ETEC, and EAEC is consistent with large-scale studies showing a limited association between their quantities and diarrhea.